Historical and statistical data on the development of the domestic alcoholic beverages industry - S. A. Khurshudyan; K. V. Kobelev; A. E. Ryabova (Пищевые системы)
The method of historical and statistical data analysis makes it possible to identify development and characteristic patterns, both temporary and permanent, production criteria for various branches of the food industry. The application of this method made it possible to trace formation of the alcohol industry inRussiaand identify critical historical events that influenced its development. The article presents and analyzes statistical data on the production of the main types of alcoholic beverages industry since 1913.